Particularities schizophrenia spectrum disorder with using cannabinoids - Kramar Юлія (Psychosomatic Medicine and General Practice, 2018)
Schizophrenia is a mental illness characterized by abnormal behavior, strange speech, and a decreased ability to understand reality. Other symptoms may include false beliefs, unclear or confused thinking, hearing voices that do not exist, reduced social engagement and emotional expression, and lack of motivation. Disorders of the schizophrenia spectrum are polyetiological and multifactorial. Under the influence of environmental factors is changing the clinical picture of schizophrenia. Scientists have noted that psychoactive substance use is associated with a less favorable course of schizophrenia and more severe neurocognitive impairment. Based on a recent study, the features of clinical polymorphism of schizophrenia spectrum disorders under the influence of cannabinoid use have been established. Thus, in patients with cannabinoid use, schizoaffective disorders with a predominantly manic variant are more commonly observed; in the clinical picture, delusions, hallucinations, arousal, and anxiety predominate, as well as a better level of social functioning compared to patients with no action given. This study presents a clinical case with a picture of disorders of the schizophrenia spectrum for cannabinoid use. In particular, the leading syndrome in the clinical picture was manic, and schizoaffective disorder was established in the initial stages of the disease. Pathopsychological diagnostics showed disturbance of dynamics of mental processes in the form of acceleration of their pace; disturbance of purposeful thinking, distortion of processes of generalization and distraction, slippage on paralysis, latent signs; emotional paradox; inadequate self-esteem. Symptoms of schizophrenia were quite abolished during periods of remission but pronounced during exacerbation. In the period of remissions, the most prominent were disturbances of thinking in the form of stereotyping and resonance, unusual content of thoughts. In this clinical case, a high level of social functioning is generally demonstrated. Thus, the recommended measures of secondary and primary prevention in this particular case are the prevention and further exclusion of cannabinoids, timely treatment of the first psychotic symptoms and appropriate treatment of affective disorders and psychotherapeutic interventions for emotional support in crises.